Open Source Law, Policy and Practice Second Edition - Brock, Amanda (Oxford University Press, 2022)
This book examines various policies, including the legal and commercial aspects of the Open Source phenomenon. Here, 'Open Source' is adopted as convenient shorthand for a collection of diverse users and communities, whose differences can be as great as their similarities. The common thread is their reliance on, and use of, law and legal mechanisms to govern the source code they write, use, and distribute. The central fact of open source is that maintaining control over source code relies on the existence and efficacy of intellectual property ('IP') laws, particularly copyright law. Copyright law is the primary statutory tool that achieves the end of openness, although implemented through private law arrangements at varying points within the software supply chain. This dependent relationship is itself a cause of concern for some philosophically in favour of 'open', with some predicting (or hoping) that the free software movement will bring about the end of copyright as a means for protecting software.